Advance distribution of misoprostol for the prevention of postpartum hemorrhage in South Sudan. Issue 2 (9th July 2014) - Smith, Jeffrey M.; Dimiti, Alexander; Dwivedi, Vikas; Ochieng, Isabella; Dalaka, Maryrose; Currie, Sheena; Luka, Edward Eremugo; Rumunu, John; Orero, Solomon; Mungia, Jaime; McKaig, Catharine
Abstract: Objective: To determine if high uterotonic coverage can be achieved in South Sudan through a facility‐ and community‐focused postpartum hemorrhage (PPH) prevention program. Methods: The program was implemented from October 2012 to March 2013. At health facilities, active management of the third stage of labor (AMTSL) was emphasized. During prenatal care and home visits, misoprostol was distributed to pregnant women at approximately 32 weeks of pregnancy for the prevention of PPH at home births. Data on uterotonic coverage and other program outcomes were collected through facility registers, home visits, and postpartum interviews. Results: In total, 533 home births and 394 facility‐based births were reported. Misoprostol was distributed in advance to 787 (84.9%) pregnant women, of whom 652 (82.8%) received the drug during home visits. Among the women who delivered at home, 527 (98.9%) reported taking misoprostol. A uterotonic for PPH prevention was provided at 342 (86.8%) facility‐based deliveries. Total uterotonic coverage was 93.7%. No adverse events were reported. Conclusion: It is feasible to achieve high coverage of uterotonic use in a low‐resource and postconflict setting with few skilled birth attendants through a combination of advance misoprostol distribution and AMTSL at facilities. Advance distribution through home visits was key to achieving high coverage of misoprostol use.